Determining the Particle Size of Cu and Ni in Thin Cu/Ni Films using the Williamson-Hall Method - Rahmatika, Zulfa ‘Amalia; Toifur, Moh. (Journal of Novel Engineering Science and Technology, 2023)
This research focuses on analyzing the particle size of a thin Cu/Ni layer produced through electroplating by varying the input voltage. The Williamson-Hall method is used to determine the particle size of the layer, and an X-ray diffractometer is used to characterize the layer. The study finds that the particle size of Cu and Ni layers with different applied voltages has different values due to various factors. The optimum voltage for the Ni layer is found to be 7.5 volts, and its overall particle size is 4.13 × 10^(-10) nm, while the particle size of Cu is 5.00 × 10^(-9) nm. The applied voltage affects the particle size produced, and the research identifies an optimum voltage at 7.5 volts.